Pelaksanaan Pendaftaran Merek Dagang pada Usaha Mikro Kecil dan Menengah di Bukittinggi - Maesa, Isradi; Suryamizon, Anggun Lestari; Nazar, Jasman (Universitas Ekasakti, 2023)
In the industrial and trade sectors where brands are a part of intellectual property rights, they have a position as a differentiator and identity for a business, one of which is micro, small and medium enterprises (MSMEs). In order to obtain the trademark rights, every micro, small and medium enterprise actor must submit an application for trademark registration in order to obtain the trademark rights when it is used. Even though regulations regarding marks have been expressly regulated by the state in a statutory regulation, namely Law Number 20 of 2016 concerning Marks and Geographical Indications, in practice there are still many MSME actors who have not registered their trademarks. This study aims to determine the implementation and inhibition of MSME actors in Bukittinggi in registering their trademarks. The method used in this study is a qualitative method with an empirical juridical approach. The registration of MSME trademarks is fundamental to obtaining exclusive rights to brands. In addition, to register a business actor must fulfill administrative requirements for his trademark. The obstacles in registering a trademark for MSME actors in Bukittinggi are the lack of information and knowledge obtained and concerns about financing when registering their trademarks.